Knowledge of Sexually Transmitted Infections (STI’s) and HIV/AIDS among Health Cadres of ‘Aisyiyah - Ratu Matahari (Journal of Ners and Midwifery, 2020)
HIV / AIDS education needs to be done to active reproductive women such as housewives who are vulnerable populations. This research aimed to analyze differences in knowledge related to STIs and HIV / AIDS among Aisyiyah health cadres in North Banguntapan, Bantul Regency. This research is a pre-experimental research design method. The design of this research was one group pretest-posttest. The research sample was selected purposively as many as 31 respondents. This research produced information that there was a mean difference between prior and after knowledge about health education about STDs and HIV / AIDS with a significance value of 0.001 (p-value <0.05) and 95% CI of 0.466 - 1.728. Based on the results of the research it could be concluded that there was an increase of knowledge about STI and HIV / AIDS in Aisyiyah health cadres after getting health education.